Konsep perempuan shalihah pada lirik â€œAisyah Istri Rasulullahâ€ (Studi ketidakadilan analisis wacana Teun A. Van Dijk) - Kumala, Nur (Islamic Communication Journal, 2020)
The presentation of the lyrics in a song is a form of communication that requires meaning, through the massive lyrics of a song composed entitled "Aisyah Wife Rasulullah" which is discussed interestingly to be discussed in the realm of the meaning of the text, the context and the discourse. Through Teun A. Van Dijk's discourse analysis, a certain condition can also be understood as an injustice process, in which to expose the injustice it is done in 3 ways, namely by text analysis, context analysis and social discourse analysis. The importance of understanding a text with this discourse analysis is able to open a broader paradigm of problems in human life, especially the concept of injustice. As in the phenomenon of the song "Aisyah wife of the Prophet Muhammad" which produces a social discourse that women are righteous physically and who always accompany their husbands. This is said to be injustice in religion which has discussed the relationship between partners, as well as `` the measure of happiness in the household is not measured by women's physicality, as the concept of shalihah according to religion. So, the focus of this research is only to expose the injustices that occur in the text and the context of the discourse about the meaning of "shalihah" in the lyrics of "Aisyah, the wife of the Prophet".Â